Analisa Budaya Organisasi dan Lingkungan Kerja serta Dampaknya terhadap Kinerja Guru pada SMA Telkom Bandung - Sintya Mursid, Rifda; Ferdian, Ary (Rifa'Institute, 2022)
Good performance can be supported by a good organizational culture and work environment. Organizational culture and work environment can have an influence on the performance of its resources. The purpose of this study was to determine the organizational culture and work environment at Telkom Bandung High School, as well as whether organizational culture and work environment have a partial or simultaneous influence on teacher performance at Telkom Bandung High School. The method used in this study is a quantitative method. The data collection technique used in this research is to use secondary data and primary data and also conduct interviews with the Principal of Telkom Bandung High School. The sampling method used is non-probability sampling with saturated sampling. In this study, using descriptive analysis techniques and multiple linear analysis, with hypothesis testing using the T test, F test, and the coefficient of determination. Based on the results of the study and the results of responses from respondents, the variables of organizational culture, work environment, and teacher performance are at the level of the